The effect of the matrix system in the delivery and in-vitro bioactivity of microencapsulated oregano essential oil - Beirão-da-Costa, Sara (2010)
In this study, oregano essential oil (EO) was microencapsulated by spray/freeze drying in: rice starch (with/without bonding agents), gelatine/sucrose and inulin. Microencapsulates were analysed for morphology and structure, releasing ability of entrapped EO, as evaluated by diffusion coefficient (D) and bioactivity.